2014
DOI: 10.1210/jc.2014-1120
|View full text |Cite
|
Sign up to set email alerts
|

Codon Arg15 Mutations of theAP2S1Gene: Common Occurrence in Familial Hypocalciuric Hypercalcemia Cases Negative for Calcium-Sensing Receptor (CASR) Mutations

Abstract: The results affirm that a significant number of patients suspected of having FHH but proven negative for CASR mutation have AP2S1 p.R15 mutations. Screening for AP2S1 p.R15 mutations in such cases should be considered, given the clinical benefits (avoiding unnecessary parathyroidectomy) that have already been demonstrated for CASR screening in FHH1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
3
26
1
1
Order By: Relevance
“…AP2s has a pivotal role in clathrin-mediated endocytosis of GPCRs such as the CaSR, and to date more than 50 FHH3 patients with AP2s mutations, which are all missense mutations involving the Arg15 residue (Arg15Cys, Arg15His and Arg15Leu), have been reported. (12)(13)(14)(15)(16) Approximately 65% of FHH patients will have a CaSR mutation, 5% an AP2s mutation, <1% a Ga 11 mutation, and the remaining $30% of FHH patients are considered to have involvement of a genetic abnormality that remains to be identified. Here we report the identification of a novel Ga 11 mutation in a patient with FHH in whom CaSR and AP2s mutations had been previously excluded.…”
Section: ) With Rapid Increase In Intracellular Calciummentioning
confidence: 99%
“…AP2s has a pivotal role in clathrin-mediated endocytosis of GPCRs such as the CaSR, and to date more than 50 FHH3 patients with AP2s mutations, which are all missense mutations involving the Arg15 residue (Arg15Cys, Arg15His and Arg15Leu), have been reported. (12)(13)(14)(15)(16) Approximately 65% of FHH patients will have a CaSR mutation, 5% an AP2s mutation, <1% a Ga 11 mutation, and the remaining $30% of FHH patients are considered to have involvement of a genetic abnormality that remains to be identified. Here we report the identification of a novel Ga 11 mutation in a patient with FHH in whom CaSR and AP2s mutations had been previously excluded.…”
Section: ) With Rapid Increase In Intracellular Calciummentioning
confidence: 99%
“…FHH-2 and FHH-3 are associated, respectively, with germline inactivating mutations of GNA11 (19p13.3) and AP2S1 (19q13.2) genes 13 32 88 90 91 141 185 . GNA11 gene encodes the α-subunit of G 11 , one of the principal G proteins activating CaSR signalling pathway, whereas AP2S1 gene encodes the adaptor protein 2 σ-subunit involved in CaSR endocytosis 13 32 88 90 91 141 185. Both mutations in GNA11 and AP2S1 genes cause hypocalciuric hypercalcaemia though aberrant inactivation of CaSR signalling, similar to FHH-1 13 32 88 90 91 141 185.…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…GNA11 gene encodes the α-subunit of G 11 , one of the principal G proteins activating CaSR signalling pathway, whereas AP2S1 gene encodes the adaptor protein 2 σ-subunit involved in CaSR endocytosis 13 32 88 90 91 141 185. Both mutations in GNA11 and AP2S1 genes cause hypocalciuric hypercalcaemia though aberrant inactivation of CaSR signalling, similar to FHH-1 13 32 88 90 91 141 185. Phenotypically and pathologically, patients with FHH-2 typically present with features indistinguishable from FHH-1, whereas those with FHH-3 tend to present with osteomalacia, higher levels of PTH and more frequent parathyroid gland involvement (hyperplasia) 3 13 32 42 88 90 91 141 185…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…Homozygous CASR mutations leading to only a mild overall impairment of extracellular calcium sensing may cause a FHH-like phenotype (8,12,13,14), whereas heterozygous CASR mutations causing more pronounced functional impairment can lead to neonatal hyperparathyroidism (NHPT) (15,16,17). Recently it has been found that inactivating mutations in the CASR associated G protein alpha 11 (GNA11) and in the adaptor-related protein complex 2 sigma 1 subunit (AP2S1) can also cause familial hypocalciuric hypercalcemia (FHH types 2 and 3) (18,19,20).…”
Section: Mutations Causing Loss Of Casr Functionmentioning
confidence: 99%